FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KUALITA AUDIT AUDITOR INDEPENDEN PADA KANTOR AKUNTAN PUBLIK (KAP) DI JAWA TENGAH (Students' Journal of Accounting and Banking, 2015)
This research aims to analyze the effect of the independence, experience, due professional care, accountability, and integrity to quality audits. In this study population taken was an auditor who works at the public accountant in Central Java, with a total sample of 51 respondents.Analytical tools used in this study is the analysis of Multiple Linear Regression. The results showed that independence has a positive influence on quality auditing. Experience, due professional care and accountability also has a positive influence to the quality of audits. The integrity of the auditors audit quality proven effect.Keywords: Audit Quality, Independence, Experience, Due Professional Care, Accountability, and Integrity